APLIKASI ONLINE PENGELOLAAN TUGAS OTOMATIS MENGGUNAKAN METODE RAPID APLICATION DEVELOPMENT - Alfred Tenggono; Imroatul Khasanah (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2022)
Online learning that is currently running in the world of education has its own difficulties for a teacher, especially in the collection, management and recapitulation of student assignments. The average task collection uses a message sharing application where this application does not have the ability to manage and recapitulate the collected tasks. Constraints that occur can be corrected by creating an application that can be used for the process of collecting tasks and presenting data automatically for online learning support. The purpose of this study is to build an automatic application that is used for task collection, data processing, data presentation and automatic warning if students have not submitted their assignments. The development of this research implements the RAD method to complete the system development¸ with the stages of requirements planning, modeling from users, and development or implementation. This research produces an application for managing and reporting student assignments that can help teachers in the teaching process, which is integrated with a telegram bot that can assist in the process of collecting assignments and reminders to students or parents of students.